A Prospective Study of Circulating Chemokines and Angiogenesis Markers and Risk of Multiple Myeloma and Its Precursor. Issue 2 (16th December 2019) - Hofmann, Jonathan N; Landgren, Ola; Landy, Rebecca; Kemp, Troy J; Santo, Loredana; McShane, Charlene M; Shearer, Joseph J; Lan, Qing; Rothman, Nathaniel; Pinto, Ligia A; Pfeiffer, Ruth M; Hildesheim, Allan; et al.
Abstract: Background: Experimental and clinical studies have implicated certain chemokines and angiogenic cytokines in multiple myeloma (MM) pathogenesis. To investigate whether systemic concentrations of these markers are associated with future MM risk and progression from its precursor, monoclonal gammopathy of undetermined significance (MGUS), we conducted a prospective study within the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial. Methods: We measured concentrations of 45 immunologic and pro-angiogenic markers in sera from 241 MM case patients, 441 participants with nonprogressing MGUS, and 258 MGUS-free control participants using Luminex-based multiplex assays and enzyme-linked immunosorbent assays. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using multivariable logistic regression. We also evaluated absolute risk of progression using weighted Kaplan-Meier estimates. All statistical tests were two-sided. Results: Prediagnostic levels of six markers were statistically significantly elevated among MM case patients compared with MGUS-free control participants using a false discovery rate of 10% (EGF, HGF, Ang-2, CXCL12, CCL8, and BMP-9). Of these, three angiogenesis markers were associated with future progression from MGUS to MM: EGF (fourth vs first quartile: OR = 3.01, 95% CI = 1.61 to 5.63, P trend = .00028), HGF (OR = 2.59, 95% CI = 1.33 to 5.03, P trend = .015), and Ang-2 (OR = 2.14, 95% CI = 1.15 to 3.98, P trend = .07). A composite angiogenesis biomarker score substantially stratified risk of MGUS progression to MM beyond established risk factors for progression, particularly during the first 5 years of follow-up (areas under the curve of 0.71 and 0.64 with and without the angiogenesis marker score, respectively). Conclusions: Our prospective findings provide new insights into mechanisms involved in MM development and suggest that systemic angiogenesis markers could potentially improve risk stratification models for MGUS patients.